2021
DOI: 10.1186/s12948-021-00147-8
|View full text |Cite
|
Sign up to set email alerts
|

Small airway dysfunction and poor asthma control: a dangerous liaison

Abstract: Asthma is a common chronic condition, affecting approximately 339 million people worldwide. The main goal of the current asthma treatment guidelines is to achieve clinical control, encompassing both the patient symptoms and limitations and the future risk of adverse asthma outcomes. Despite randomized controlled trials showing that asthma control is an achievable target, a substantial proportion of asthmatics remain poorly controlled in real life. The involvement of peripheral small airways has recently gained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 117 publications
4
26
0
Order By: Relevance
“…These data highlight a significant effect of mepolizumab on airflow limitation in the peripheral airways. Indeed, in real-world settings, FEF25-75 is considered to be the most commonly used spirometric indicator of small airway patency in real-life clinical practice [ 28 ]. Within the context of the Severe Asthma Research Program (SARP) project, it was observed that some severe asthmatic patients who had a more severe reduction of FEF25-75 also displayed more symptoms and a greater need for medication, as well as higher FeNO levels, total serum IgE concentrations, and bronchial hyperresponsiveness [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data highlight a significant effect of mepolizumab on airflow limitation in the peripheral airways. Indeed, in real-world settings, FEF25-75 is considered to be the most commonly used spirometric indicator of small airway patency in real-life clinical practice [ 28 ]. Within the context of the Severe Asthma Research Program (SARP) project, it was observed that some severe asthmatic patients who had a more severe reduction of FEF25-75 also displayed more symptoms and a greater need for medication, as well as higher FeNO levels, total serum IgE concentrations, and bronchial hyperresponsiveness [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…SAD was previously linked to some clinical phenotypes of patients, i.e., active smokers, elderly patients with long duration of asthma and presence of fixed airflow obstruction, patients with nocturnal and exercise-induced symptoms, severe/uncontrolled asthma ( 13 16 ). The limit of most of the available studies is that they analyze the association of single features with SAD, instead ofcomprehensively address multiple asthma features associated with SAD.…”
Section: Association Of Sad With Specific Asthma Phenotypes and Poor ...mentioning
confidence: 99%
“…We previously reviewed the prevalence and negative impact of SAD on asthma control, without addressing the position of current international guidelines on the role of SAD in asthma ( 13 ). In recent years, several original studies and systematic reviews confirmed that SAD is associated with, among others, greater bronchial hyper-responsiveness, worse asthma control and severity, more nocturnal and exercise-induced symptoms, and a higher number of exacerbations ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…IOS is not a new technology ( 76 ), but more recent portable units facilitate its use beyond the pulmonary function laboratory, including field studies of the workplace. IOS measures the mechanical properties of the respiratory system including upper and intrathoracic airways, lung tissue and chest wall, specifically respiratory impedance, and is thought to be sensitive for dysfunction of the small airways ( 77 , 78 ). Histopathological changes in small airways of workers exposed to alpha-diketones are characterized by bronchiolar wall fibrosis, leading to luminal narrowing and obliteration that obstructs airflow ( 79 ).…”
Section: Methods and Discussionmentioning
confidence: 99%
“…IOS measures the mechanical properties of the respiratory system including upper and intrathoracic airways, lung tissue and chest wall, specifically Are you ever within an arm's length of these locations/units? Coffee roaster, cooling bins of roasted coffee, grinder, hoppers or containers of roasted coffee, coffee being packaged, packaged coffee, flavoring is being added or mixed respiratory impedance, and is thought to be sensitive for dysfunction of the small airways (77,78). Histopathological changes in small airways of workers exposed to alpha-diketones are characterized by bronchiolar wall fibrosis, leading to luminal narrowing and obliteration that obstructs airflow (79).…”
Section: Health Assessment Strategymentioning
confidence: 99%